Meteorological observations for Europe and the southern Mediterranean region, 1877-2012 - Linden Ashcroft; Joan Ramon Coll; Alba Gilabert; Peter Domonkos; Enric Aguilar; Javier Sigro; Merce Castella; Per Unden; Ian Harris; Phil Jones; Manola Brunet (PANGAEA, 2018)
Under the auspices of Work Package 1 of the European Union funded Uncertainties in Ensembles of Regional ReAnalysis (UERRA) project, we present a digital dataset of 8.8 million subdaily meteorological observations rescued across the European and the southern Mediterranean region. Data from 127 stations and of 15 climate variables (many of them Essential Climate Variables as defined by the Global Climate Observing System) in the northern Africa and European sectors have been recovered for the period 1877 to 2012. Quality control of the data using a two-step semi-automatic statistical approach identified 3.5% of observations that required correction or removal, on par with previous data rescue efforts. Here we provide all versions of the rescued dataset to ensure it is as traceable as possible: the transcribed data in original units (in the original files); data at each stage of quality control (in the original files); and the final values in SI units, along with quality control flags and conversion methods. The original scanned images are available through the Universitat Rovira i Virgili Centre for Climate Change (http://www.c3.urv.cat/). Further details of the dataset development are provided in the associated peer-reviewed publication.
Supplement to: Ashcroft, Linden; Coll, Joan Ramon; Gilabert, Alba; Domonkos, Peter; Brunet, Manola; Aguilar, Enric; Castella, Merce; Sigro, Javier; Unden, Per; Harris, Ian; Jones, Phil (2018): A rescued dataset of sub-daily meteorological observations for Europe and the southern Mediterranean region, 1877-2012. Earth System Science Data, 10(3), 1613-1635, https://doi.org/10.5194/essd-2018-39